Speciation and Bioavailability of Heavy Metals Pb and Cd in Palu Bay Sediments after the Earthquake and Tsunami - Sosidi, Husain; Khairuddin; Ruslan; Abustiana, Rahma Lolita; Ramli, Aksar; Rahim, Erwin Abdul (Chemistry Department, Mathematics and Natural Science Faculty, Tadulako University, 2025)
Major disturbances to seafloor morphology and input of terrestrial material due to the earthquake- tsunami in Palu City in 2018 have the potential to alter the chemical form (speciation), bioavailability, and flux of lead (Pb) and cadmium (Cd) in Palu Bay sediments. This study was conducted to analyze the speciation of Cd2+ ions and Pb2+ ions and determine the concentration of elusion ions using Diffusive Gradient in Thin Film (DGT). In this study, two methods were carried out, namely the fractionation method and the DGT method. The results showed that the analysis of ion speciation at 3 locations using the fractionation method obtained the highest concentration of Cd2+ ions of 1.4492 mg/L at location 1 and the highest concentration of Pb2+ ions of 0.0200 mg/L at location 3. The results of ion analysis at 3 locations using the DGT method obtained the highest elution yield concentration of Cd2+ ions of 0.0225 mg/L at location 1 and the highest elution yield concentration of Pb2+ ions of 0.0155 mg/L at location 3. This study shows that the presence of heavy metals Pb and Cd in Palu Bay sediments after the earthquake-tsunami is still detected with varying concentrations between locations. The fractionation method is able to describe the distribution of metal speciation in sediments, while the DGT method provides information on labile fractions that are more relevant to bioavailability. The combination of these two methods is important for understanding the potential risk of heavy metals to Palu Bay aquatic ecosystems and can be used as a basis for post-disaster environmental monitoring and management efforts.